2008
DOI: 10.1016/j.ymgme.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of pyruvate carboxylase deficiency: Mosaicism correlates with prolonged survival

Abstract: Pyruvate carboxylase (PC) deficiency (OMIM, 266150) is a rare autosomal recessive disease. The revised PC gene structure described in this report consists of 20 coding exons and four non-coding exons at the 5'-untranslated region (5'-UTR). The gene codes for three transcripts due to alternative splicing: variant 1 (NM_000920.3), variant 2 (NM_022172.2) and variant 3 (BC011617.2). PC deficiency is manifested by three clinical phenotypes -an infantile form (Type A), a neonatal form (Type B), and a benign form (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
(57 reference statements)
6
32
1
Order By: Relevance
“…In contrast to our study, Wang et al [19] compared the 5′-UTR sequences of three human PC mRNA variants namely, variant 1 (NM_000920.3), 2 (NM_022172.2) and 3 (BC011617.2) deposited at the NCBI database to the genomic sequence of human PC gene and concluded that these variants are alternatively spliced from four 5′-UTR exons, i.e. UE1, UE2, UE3 and UE4, respectively, with the distal, middle and proximal promoters located immediately upstream of exons UE1, UE2 and UE4, respectively [19].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Wang et al [19] compared the 5′-UTR sequences of three human PC mRNA variants namely, variant 1 (NM_000920.3), 2 (NM_022172.2) and 3 (BC011617.2) deposited at the NCBI database to the genomic sequence of human PC gene and concluded that these variants are alternatively spliced from four 5′-UTR exons, i.e. UE1, UE2, UE3 and UE4, respectively, with the distal, middle and proximal promoters located immediately upstream of exons UE1, UE2 and UE4, respectively [19].…”
Section: Resultscontrasting
confidence: 99%
“…However, the regulatory regions of the PC gene that confer tissue-specific expression of PC in humans are not known. Recently, Wang et al [19] reported that unlike the rat and mouse PC genes, the human PC gene is transcribed from three promoters. Herein, we present evidence that similar to the rodent PC genes, the human PC gene is transcribed from two promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Two forms of human pyruvate carboxylase cDNAs have been identified in the liver that share the coding region but differ in their 5´ untranslated regions, suggesting that they are generated by alternative splicing of the primary transcript (Jitrapakdee, et al, 1996. A revision of the pyruvate carboxylase gene structure confirms the occurrence of alternative splicing that generates three transcripts and therefore three pyruvate carboxylase enzyme variants (Wang, et al, 2008). Kinetic analysis demonstrates that the recombinant human pyruvate carboxylase has the same properties as the native enzyme isolated from liver autopsy (Jitrapakdee, et al, 1996.…”
mentioning
confidence: 89%
“…Tissue heterogeneity in the expression of the enzyme and increased residual enzyme activity in vivo have been offered as possible explanations. (Stern, et al, 1995, Wang, et al, 2008 Mosaicism has been found in most cases of pyruvate carboxylase deficiency with prolonged survival. (Wang, et al, 2008) A Recently, nuclear location of muscle fructose 1,6-bisphosphatase has been reported.…”
Section: Human Tissue Distribution Of Pdh Kinases and Phosphatasesmentioning
confidence: 99%
See 1 more Smart Citation